Platelet desialylation correlates with efficacy of first-line therapies for immune thrombocytopenia. Issue 1 (December 2017) - Tao, Lili; Zeng, Qingshu; Li, June; Xu, Miao; Wang, Jiajia; Pan, Ying; Wang, Huiping; Tao, Qianshan; Chen, Yang; Peng, Jun; Hou, Ming; Jansen, Arend; et al.
Abstract Immune thrombocytopenia (ITP) is a common autoimmune bleeding disorder. Despite considerable investigation, the pathogenesis of ITP remains incompletely understood, and for many patients, effective therapy is still unavailable. Using murine models and in vitro studies of human blood samples, we recently identified a novel Fc-independent platelet clearance pathway, whereby antibody-mediated desialylated platelets can be cleared in the liver via asialoglycoprotein receptors, leading to decreased response to standard first-line therapies targeting Fc-dependent platelet clearance. Here, we evaluated the significance of this finding in 61 ITP patients through correlation of levels of platelet desialylation with the efficacy of first-line therapies. We found that desialylation levels between different responses to treatment groups were statistically significant (p  < 0.01). Importantly, correlation analysis indicated response to treatment and platelet desialylation were related (p  < 0.01), whereby non-responders had significantly higher levels of platelet desialylation. Interestingly, we also found secondary ITP and certain non-ITP thrombocytopenias also exhibited significant platelet desialylation compared to healthy controls. These findings designate platelet desialylation as an important biomarker in determining response to standard treatment for ITP. Furthermore, we show for the first time platelet desialylation in other non-ITP thrombocytopenias, which may have important clinical implications and deserve further investigation.